Ferromagnetic property in Transition Metal (Mn, Fe, Ni)-Doped SnO2 for Spintronic Applications: A Review of Computational and Experimental Studies - Baral, Mandakini; Patnaik, Padmaja; Nayak, Santanu Kumar; Das, Dipan Kumar (Physics and Chemistry of Solid State, 2024)
The development of room temperature ferromagnetic property (RTFM) in TM doped SnO2 has potential application in the field of spintronic, recently attracted attention. This material exhibits exceptional chemical stability, demonstrates N-type behavior with a high carrier density, and remarkably displays long-range ferromagnetic properties. However, the mechanism behind this ferromagnetic property (FM) is still not fully understood. Numerous surveys of the literature have indicated that factors such as the presence of oxygen vacancies, defects, type and concentration of dopants, temperature, and methods used for sample preparation have a notable impact on the performance of FM. Here we reviewed the FM mechanism which is noticed in Iron, Nickel, Manganese doped Tin dioxide material both experimental and computational method.